(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper titled "Strategic Employee Retention in Indian IT: Leveraging Experience to Enhance Retention Strategies" investigates the critical role of employee experience in shaping effective retention strategies within the dynamic landscape of the Indian Information Technology (IT) industry. The study employs convenience sampling, allowing for a comprehensive analysis of 518 employees from various IT companies in India. Through the application of ANOVA (Analysis of Variance) analysis, this research explores the relationship between employee experience levels and the implementation of retention strategies.